"STRATEGIC PROGNOSTICATION OF INTERNATIONAL RELATIONS" - E. T. Mekhdiev (Vestnik MGIMO-Universiteta)
Book review: Strategic prognostication of international relations: the count. monograph / ed. A.I., Podberezkin, M.V. Aleksandrov; [A. Podberezkin I. et al.]; Moscow State Institute of International Relations (University), Ministry of Foreign Affairs of the Russian Federation the Center for Military-Political Studies. - M.: MGIMO-University, 2016. - 743 p.